Design and development of a versatile domestic ironing board - Tan, Jolene Zi Ling (Nanyang Technological University, 2021)
The ironing board is a hundred-year-old invention that has managed to retain its youthful visage, in that it has hardly changed since its conception. Today we are very used to the crisscross legged, tapered ironing board that has become the standard design since the 1940s. With the little innovation efforts put towards the ironing board, this project aims to revisit and redesign the device. The objective of this project is to design a versatile domestic ironing board. This project involves the conception of ideas that can increase versatility and the subsequent systematic process used to evaluate, select, and develop the ideas. The stages in this process are conceptual design, embodiment design and detailed design. At the end of this process, the design then undergoes force analysis. A prototype is also created at the end of this project.